2021
DOI: 10.3390/ma14195893
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Mechanical Properties and the Cytocompatibility for the PMMA Nanocomposites Reinforced with the Hydroxyapatite Nanofibers and the Magnesium Phosphate Nanosheets

Abstract: Commercial poly methyl methacrylate (PMMA)-based cement is currently used in the field of orthopedics. However, it suffers from lack of bioactivity, mechanical weakness, and monomer toxicity. In this study, a PMMA-based cement nanocomposite reinforced with hydroxyapatite (HA) nanofibers and two-dimensional (2D) magnesium phosphate MgP nanosheets was synthesized and optimized in terms of mechanical property and cytocompatibility. The HA nanofibers and the MgP nanosheets were synthesized using a hydrothermal hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Shirdar et al have prepared PMMA modified with HA nanofibers and 2D magnesium phosphate nanosheets, so accelerating bone healing and osseointegration. The authors demonstrated the improving of the cytocompatibility and optimum compressive strength of the nanohybrid composite compared to PMMA [ 76 ].…”
Section: Polymethacrylate: Applicationsmentioning
confidence: 99%
“…Shirdar et al have prepared PMMA modified with HA nanofibers and 2D magnesium phosphate nanosheets, so accelerating bone healing and osseointegration. The authors demonstrated the improving of the cytocompatibility and optimum compressive strength of the nanohybrid composite compared to PMMA [ 76 ].…”
Section: Polymethacrylate: Applicationsmentioning
confidence: 99%
“…Intensive research is currently being conducted to improve the thermal, mechanical and biological properties of bone cements [ 16 ]. The research includes doping the cement mass with small amounts of components such as carbon fibers [ 41 ], zirconia fibers [ 42 ], graphite fibers [ 43 ], graphene oxide [ 44 , 45 , 46 , 47 ], bioactive glasses [ 48 ], nanosilver [ 49 ], polydioxanone (PDO) [ 48 ], cellulose [ 48 , 50 , 51 ], mesoporous silica nanoparticles [ 52 , 53 ], aramid [ 54 , 55 ], polyethylene [ 56 ], titanium [ 57 , 58 ], ultra-high molecular weight polyethylene [ 59 ], tricalcium phosphate (TCP) [ 16 , 60 ] or hydroxyapatite (HA) [ 61 , 62 ]. The effect of aging processes associated with the absorption of physiological fluids and the accompanying hydrolysis of polymethylmethacrylate (PMMA) occurring in the outermost layers of the cement are also important, as well as the effect of deviation from the manufacturer’s recommended cement mix ratio [ 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties only depend on the features of the fibers, such as the smaller diameters and fewer beads [ 24 ]. Fibers produced with smaller diameters will have better mechanical properties, such as a higher Young’s modulus, better strength, and more toughness [ 25 , 26 , 27 , 28 ]. With the electrospinning technique, fiber properties such as the diameter, alignment, degree of fusion, and porosity can be controlled and enhanced [ 24 ].…”
Section: Introductionmentioning
confidence: 99%